Safety as One of the Most Important Components of the Digital Competence System in Wartime Conditions - HLAVCHEVA, Y. M.; ODNOVOLYKOVA, O. V.; NOVOSOLOVA, S. Y. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2022)
Objective. To determine the place of safety skills in the system of digital competences and the role of the university library in their formation among users. The acquisition of safety skills in working with information will allow users to level out and control the negative impact of external information factors. Among the factors that negatively affect a person, there is a colossal amount of information, consisting of actual, relevant, and useful information, as well as garbled, fake, manipulative, and destructive ones. Methods. Empirical methods have been used in the investigation. The practical experience and recommendations of international and national experts in the direction of the formation of safety skills in working with information have been analyzed. The level of their implementation by the library at this stage has been monitored. Result. It has been determined that for the qualitative and integral formation of users’ safety skills in working with information, it is necessary to expand the list of activities and topics in the direction of their popularization and training. The acquisition of safety basics of working with information will allow users to restore and maintain control over physical and psychological health. Conclusions. So, the ability to safely interact with information is one of the most important components of the digital competence system of users, which is especially important in wartime conditions. Teaching such competences will help users to realize, control, and level out the negative impact of external information factors, and that’s why it can be considered an urgent task for libraries as institutions that are competent to work with information.